Long-term assessment of clinical response to adalimumab therapy in refractory ulcerative colitis. Issue 2 (February 2016) - Hussey, Mary; Mc Garrigle, Robert; Kennedy, Una; Holleran, Grainne; Kevans, David; Ryan, Barbara; Breslin, Niall; Mahmud, Nasir; McNamara, Deirdre
Abstract : Introduction: The role of antitumour necrosis factor agents, in particular infliximab in ulcerative colitis (UC) has been well established. More recently adalimumab, a fully humanized antitumour necrosis factor α monoclonal antibody, was licensed for refractory moderately active UC in 2012. Available outcome data for adalimumab from routine clinical practice is limited. Aims: To evaluate the clinical response and remission to adalimumab in a cohort of UC patients. Methods: Patients with UC treated with adalimumab were identified from our inflammatory bowel disease database from 2007. A retrospective chart review was undertaken. Demographic and clinical data were recorded including a Mayo score and C-reactive protein (CRP) where available. All patients received standard induction subcutaneous therapy (160/80/40 mg) followed by a maintenance dose of 40 mg fortnightly. Clinical and biochemical response was assessed at 6 and 12 months. Clinical response was defined by a reduction in Mayo score more than or equal to 3, whereas clinical remission was defined by a total score of 2 or less. Dose adjustments and adverse events were also noted. Results: In all, 52 patients were identified. Of these, 65% ( n =34) were male and the mean age was 45 years (range 23–72 years). A total of 65% ( n =34) had left sided disease, 31% ( n =16) pancolitis and 4% ( n =2) proctitis. The majority commenced adalimumab due to a loss of response to immunomodulator therapy ( n =45, 87%), whereas the remaining 13% ( n =7) had loss of response or been intolerant to infliximab. The mean disease duration was 8 years (1–29 years). At baseline 85% ( n =44) had moderate disease and 15% ( n =8) had mild disease. The baseline mean CRP was 13.5 mg/l (range 1–82 mg/l) and the mean Mayo score was 6 (range 4–10). The mean duration of treatment was 18.5 months (range 4–95 months). Follow-up data was available in 46 (88%) and 37 (71%) patients at 6 and 12 months. Overall there was a statistically significant improvement in mean partial Mayo score on follow-up; 6 months=2 [ P =0.0001, 95% confidence interval (CI) 2.99–4.55], 12 months=2 ( P =0.0001, 95% CI 2.74–4.46). While 65% ( n =34) and 52% ( n =27) had a clinical response at 6 and 12 months, respectively, 52% ( n =27) and 42% ( n =22) were in remission. Overall mean CRP normalized at 6 months ( P =0.002, 95% CI 3.31–15.1). Of note 25% ( n =13) required dose escalation during follow-up, while treatment was discontinued by seven patients, five (71%) due to a loss of response, the remaining two (29%) due to an adverse event. Conclusion: Our study shows adalimumab is an effective and safe long-term therapy for moderately active UC refractory to other treatments. While this data is encouraging, further work is required on patient selection and to determine the impact of treatment on both natural history and quality of life.